Inﬂuence of English conversational clubs on speech anxiety (2024)
This research described how English conversational clubs affect speech anxiety in eleventh-grade EFL students of a public school in Medellín. This was a qualitative research focused on a case study. The sample included six eleventh-grade students from a public school in Medellín, Antioquia. Data was collected using conversation clubs, interviews, and focus groups. The results showed that the manifestation of anxiety in EFL learners can be a negative factor in their learning process. However, when the topic of the conversation is of interest to them, students tend to do better in the language. Also, using different methods and activities to practice the language can help reduce anxiety and improve their English proficiency. The study recommends that English teachers seek strategies and implement activities to promote students' speech development by creating a comfortable and stress-free environment using strategies.